Community-Based Education: Implementation of Community Service Programs in Villages - Rahmawati, Lilis; Sulaeman, Maryam; Cahyono, Cahyono; Setiadi, Tatak (Bisma : Bimbingan Swadaya Masyarakat, 2025)
This community-based service program aims to empower the community through education integrated with local needs. In Desa Sidoharjo, the program engages residents in every stage of organizing and implementing educational activities. The community-based approach is applied to address educational challenges in the village. Using Participatory Action Research (PAR), students and community members collaborate in research and action to improve the quality of education. The program includes training for local teachers, the development of a curriculum based on local needs, and the establishment of community-based learning groups. The results show an increase in community participation in educational activities and a deeper understanding of the importance of education. This service program highlights the effectiveness of community-based education in fostering long-term, sustainable development in rural areas.